Clinico-social parameters of diabetes among patientsutilizing emergency medical services - Prasad A., Rajhans; Priya Y., Kulkarni; Dhananjay S., Kelkar; Sameer A., Jog; Gouri, Ranade; Sonal, Utpat; Varsha, Hande (International Journal of Research in Medical Sciences, 2016)
Background: Diabetes mellitus (DM) is increasing in its potential in developing countries. Rise in diabetic patients calling emergency medical services (EMS) is expected. It calls for thorough assessment of patients with DM utilizing EMS. In the present study, was to assess magnitude of DM among patients utilizing EMS and its clinico-social parameters. Methods: It was hospital record based observational study of patients calling EMS delivered by a tertiary care hospital in Pune, Maharashtra, India during 1st January 2013 to 31st December 2014. Patients with incomplete records were excluded. A person with medical background was trained to extract required information from hospital records. Patients with previously diagnosed DM were considered those who were on diet, oral hypoglycemic agents or taking insulin therapy and newly diagnosed patients with DM were considered those with the value of glycemia on admission >200 mg/dl in first 24 hours. Data analysis was done using SPSS 15.0 software. Results: 45.8% (894/1951) were Patients with DM out of that 78.19% (699/894) were known to have DM while 28.81% (195/1951) were new cases of DM. 5.1% (100/1951) patients had uncontrolled DM. DM was significantly more in >60 years age group and in urban residents (p<0.001). Patients with DM were significantly more to have breathlessness, altered sensorium and dyspnoea as major purpose to call EMS (p<0.001, <0.001 and 0.045 respectively). Other co-morbidities in the form of Hypertension, other cardiovascular abnormalities, COPD, CKD and history of CVA were significantly more among Patients with DM (p<0.001, except for COPD, p=0.027). Conclusions: There was a high burden of patients with DM on EMS. EMS teams should be well trained to diagnose and manage such emergencies. Mass awareness of screening for DM and its proper management will help to decrease such burden.